Alloying of AuNPs with palladium: A promising tool for tuning of selectivity for epoxide in oxidation of styrene using molecular oxygen - Sharma, Anuj S.; Kaur, Harjinder (Applied catalysis. A, General, 2017)
[Display omitted] •Epoxidation of styrene on gold and Au-Pd alloy nanoparticles using molecular oxygen.•Lowest catalyst quantity 0.038mmol%.•98% conversion with 75% selectivity for epoxide.•A green protocol with general applicability. Present investigation, deals with synthesis of gold and gold palladium alloy nanoparticles and their application to epoxidation of styrene using molecular oxygen. Synthesized AuNPs@ Resin and bimetallic Au-Pd NPs@ Resin of average size <5nm were analyzed by various techniques such as X-ray diffraction (XRD), SEM-EDX, TEM-EDS, inductively coupled plasma atomic emission spectroscopy (ICP-AES) and X-ray photoelectron spectroscopy (XPS). Results showed that alloying of Au with Pd enhanced selectivity of the catalyst towards epoxidation. Au/Pd molar ratio (1/1) provided 98% conversion of styrene with 75% selectivity towards styrene oxide with a TOF of 0.181 (s−1) in terms of gold present in catalyst. The catalyst is promising candidate for industrial application as it showed remarkable stability, reusability and general applicability.